Immune responses to SARS-CoV-2 in vaccinated patients receiving checkpoint blockade immunotherapy for cancer - Piening, Alexander; Ebert, Emily; Khojandi, Niloufar; Alspach, Elise; Teague, Ryan M. (Frontiers in Immunology, 2022)
ABSTRACT Vaccination against SARS-CoV-2 has been successful in protecting patients with cancer from severe infections, but how immune responses against COVID-19 vaccination interact with those elicited during cancer immunotherapy has not been fully described. Immune checkpoint blockade (ICB) disrupts inhibitory pathways in immune cells to improve function and induce tumor immunity but can often cause serious immune related adverse events (IRAEs). Because COVID-19 vaccination and ICB both boost immune responses, it is imperative to understand if combining these regimens causes synergistic enhancement of the immune system. Specifically, whether ICB impacts anti-vaccine immunity in previously vaccinated patients is important since a large percentage of newly diagnosed cancer patients eligible for immunotherapy will have already been vaccinated against COVID-19. To address this, we investigated the influence of ICB on SARS-CoV-2-spike protein (SP) antibody titers and T cell responses in cancer patients previously vaccinated against COVID-19. Human blood samples were collected from 29 vaccinated patients and 12 unvaccinated control patients at baseline (prior to ICB) and following two rounds of ICB infusion. Anti-SARS-CoV-2-SP IgG titers and T cell responses were quantified. Compared to responses at baseline, there was no significant difference in these immune responses after immunotherapy in vaccinated individuals (P=0.4583, P=0.4571, respectively). We interpret these results as evidence that ICB immunotherapy does not significantly enhance SARS-CoV-2-specific antibody titers or T cell responses. Although our study lacks corresponding IRAE rates, the results provide humoral and cellular immunological data that support recent reports documenting the clinical safety and efficacy of COVID-19 vaccination in patients receiving ICB. Additional longitudinal prospective studies, such as the VOICE study (ClinicalTrials.gov identifier NCT04715438) and CAPTURE study (ClinicalTrials.gov identifier NCT03226886), are warranted and will provide broader safety and immunological data defining the effect of systemic cancer therapies on COVID-19 immunity.